Frail Older Individuals Maintaining a Steady Standing Position: Associations Between Sway Measurements with Frailty Status Across Four Different Frailty Instruments - Schülein S (Dove Medical Press, 2020)
Samuel Schülein,1 Cornel Christian Sieber,2,3 Karl-Günter Gaßmann,1,2 Martin Ritt2,4 1Geriatrics Centre Erlangen, Malteser Waldkrankenhaus St. Marien, Erlangen, Germany; 2Institute for Biomedicine of Aging (IBA), Friedrich-Alexander Universität Erlangen-Nürnberg (FAU), Nürnberg, Germany; 3Department of Internal Medicine, Kantonsspital Winterthur, Winterthur, Switzerland; 4Department of Internal Medicine III, Klinikum Neumarkt, Kliniken des Landkreises Neumarkt i. d. OPf, Neumarkt, GermanyCorrespondence: Martin RittInstitute for Biomedicine of Ageing (IBA), Friedrich-Alexander-Universität Erlangen-Nürnberg (FAU), Kobergerstraße 60, Nürnberg D-90408, GermanyTel +49 9181 420 3076Fax +49 9181 420 3077Email Martin.Ritt@klinikum.neumarkt.deObjective: An analysis of the relationships between static equilibrium parameters and frailty status and/or severity across four different frailty measures.Design: Cross-sectional analysis.Setting: Geriatric wards of a general hospital.Participants: One hundred twenty-three geriatric inpatients comprising 70 women (56.5%) and 53 men (42.7%) with an age range of 68– 95 years.Methods: The variation in the center of pressure (CoP), ie, the length of sway, the area of sway, and the mean speed, was assessed for different positions/tasks: 1) wide standing with eyes open (WSEO); 2) wide standing with eyes closed (WSEC); 3) narrow standing with eyes open (NSEO) and 4) narrow standing with eyes closed (NSEC), using a force plate. Frailty status and/or frailty severity were evaluated using the frailty phenotype (FP), the clinical frailty scale (CFS), the 14-item frailty index based on a comprehensive geriatric assessment (FI-CGA), and a 47-item frailty index (FI).Results: WSEO length of sway (FP, CFS, FI-CGA, FI), WSEO area of sway (FP, CFS, FI-CGA, FI), and WSEO mean speed (FP, CFS, FI-CGA, FI), WSEC length of sway (FP, FI-CGA, FI), WSEC area of sway (FP, FI-CGA, FI) and WSEC mean speed (FI-CGA, FI), NSEO length of sway (FP, FI-CGA, FI), NSEO area of sway (FP, CFS, FI-CGA, FI), and NSEO mean speed (FP, CFS, FI-CGA, FI), NSEC length of sway (FI-CGA, FI), NSEC area of sway (FI-CGA, FI) and NSEC mean speed (FI-CGA, FI) were associated with the frailty status and/or severity across the four different frailty instruments (all p < 0.05, respectively).Conclusion: Greater fluctuations in CoP with increasing frailty status and/or severity were a uniform finding across various major frailty instruments.Keywords: frailty instruments, balance quality parameters, older people